DESIGN OF LEARNING MATERIALS ON CIRCLE BASED ON MATHEMATICAL COMMUNICATION - Cita Dwi Rosita; Tri Nopriana; Isna Silvia (IKIP Siliwangi and I-MES, 2019)
Mathematical communication skills is an important role in mathematics learning. However, the importance of mathematical communication skills has not been fully realized in learning, especially circle material. Design a learning material based on mathematical communication is one way to develop this ability. The preliminary study produced the findings of an epistemological learning obstacle so that students' mathematical communication skills were still in the low category. This study aimed to analyze learning obstacle and designing learning materials based on the material mathematical communication circle. This study is design research that contained two stages of Didactical Design Research (DDR), didactic situation and metapedadidactional stage. Research result obtained are students difficulties in relating the material defining elements of the circle with their own language, identifying circle elements that were known and explaining through pictures, calculating the circumference and distance of circular objects based on problems, calculating the surface area of circular objects based on the problems, and rearrange the formula which states the relationship of circle elements. To solve that learning obstacle, we recommend some learning trajectory in a circle that useful for teachers. This design of learning material is valid and practical to implement in the classroom.